Інформаційно-комунікаційні технології у процесі підготовки фахівця з електроенергетики під час дистанційного навчання - Попова, Ірина Олексіївна; Попова, Ирина Алексеевна; Popova, Iryna; Ковальов, Олександр Вікторович; Ковалев, Александр Викторович; Kovalov, Oleksandr (ННВК «АТБ», 2021)
The peculiarities of the application of modern information and communication technologies in the educational process of TSATU on the example of the organization and conduct of lectures, laboratory classes online are considered. Features of the organization of independent work of students at studying of theoretical bases of electrical engineering at a distance format of training are opened. Conclusions and recommendations are formulated.
Keywords: information and communication technologies; distance learning; individual approach; traditional learning; independent work; self-learning; motivation; educational process